2016
DOI: 10.1016/j.bioorg.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of a potential difluoromethyl-nucleoside substrate with the fluorinase enzyme

Abstract: Exploration of a potential difluoromethyl-nucleoside substrate with the fluorinase enzyme, Bioorganic Chemistry (2015), doi: http:// dx.doi.org/10.1016/j.bioorg. 2015.11.003 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Along with lower turnover rates, the substrate scope of SAM-dependent halogenases are also limited to substrates SAM analogues, mainly 2-deoxy analogues. [47,48,202] This is often considered as one of the main reasons for not having many biosynthetic pathway engineering works reported with SAM-dependent halogenases. The fluorination chemistry in natural products, engineering fluorinases and applications of fluorinase enzymes are discussed elaborately in various recommended reviews.…”
Section: Sam-dependent Halogenasesmentioning
confidence: 99%
“…Along with lower turnover rates, the substrate scope of SAM-dependent halogenases are also limited to substrates SAM analogues, mainly 2-deoxy analogues. [47,48,202] This is often considered as one of the main reasons for not having many biosynthetic pathway engineering works reported with SAM-dependent halogenases. The fluorination chemistry in natural products, engineering fluorinases and applications of fluorinase enzymes are discussed elaborately in various recommended reviews.…”
Section: Sam-dependent Halogenasesmentioning
confidence: 99%
“…In 2016, O'Hagan's group found that fluorinase can be applied to the synthesis of 5′,5′-Difluoro-5′-deoxyadenosine. (see Scheme 2; Thompson et al 2016). Some research has also been done on the recognition of substrates by fluorinase (Yeo et al 2017;Sun et al 2018).…”
Section: (A) (B)mentioning
confidence: 99%
“…An earlier structural study of SalL in complex with ClDA and methoinine revealed a solvent-exposed channel into the active site. [38][39][40] To explore this in more detail, we obtained two structures of wild-type SalL with SAM and chloride (6RYZ, 1.50 Å), and with ClDA alone (6RZ2, 1.77 Å; Figure 2, Table S1). One significant difference in our structures compared to those obtained previously was a rotation of the sidechain of Arg243, from the solvent exposed exterior of the protein to the interior of the active site, enabling the formation of electrostatic interactions between Arg243 and the carboxylate of SAM (Figure 2, S1), and the side chain of Glu17 from the adjacent monomer.…”
mentioning
confidence: 99%